Evaluation of Tax Incentive Policy for MSMEs in the Covid-19 Pandemic Period in Improving Taxpayer Compliance at the Jakarta Kelapa Gading Primary Tax Service Office - Novianita Rulandari (Ilomata International Journal of Tax and Accounting, 2023)
Evaluation of Tax Incentive Policy for MSMEs in the Covid-19 Pandemic Period in Improving Taxpayer Compliance at the Jakarta Kelapa Gading Primary Tax Service Office based on evaluation criteria (William N. Dunn) from 6 criteria, namely effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy has been running well and by the regulations. Taxation. Inhibiting entities in the implementation of MSME tax incentive policies are MSME actors, there are obstacles in the use of such incentives, namely in the preparation and submission of realization reports and obstacles also arise from the fissures who have difficulty guiding taxpayers and there are constraints in the administrative system. The driving entity in the implementation of MSME tax incentive policy is socialization through WhatsApp media and mail media by AR, confirmation and appeal of AR to taxpayers immediately submit realization reports, provide AR guidance to taxpayers in delivering realization reports if taxpayers experience obstacles, providing opportunities to TAXPAYERS PP 23/2018 during the December Tax Period to report on the realization of incentive use during 2020.